2009
DOI: 10.1068/b34131t
|View full text |Cite
|
Sign up to set email alerts
|

Classification of changing regions using a temporal signature of local spatial association

Abstract: Spatially associated patterns are often found in geographical phenomena, since nearby entities are often more related than distant ones. Such spatial association also changes over time; hence, the temporal aspect of spatial association needs to be examined using both spatiality and temporality. This paper describes a method of modeling the temporal signatures of spatial association, and thus of grouping similar changes. We employed a Moran scatterplot to assess the local characteristics of a spatial associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…For comparison, the method of Ahn et al . () was also applied to this dataset. In order to select k * , they recommend the method of Feoli and Lausi ().…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For comparison, the method of Ahn et al . () was also applied to this dataset. In order to select k * , they recommend the method of Feoli and Lausi ().…”
Section: Resultsmentioning
confidence: 99%
“…In this simple view, each region is assigned to one of four states or one of four quadrants on the Moran scatter plot, that is, (low, low), (low, high), (high, low) and (high, high) where the first part refers to the region itself and the second refers to its neighbours. Recently, it has been suggested that time can be incorporated into this setting by breaking time into discrete regions and considering a sequence of local Moran statistics over time (Ahn et al ., ). This approach summarises the data as many sequences of discrete variables with four states.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Autocorrelation on a global and local level is assessed and further processed utilizing the concept of Moran scatterplots. Introduced as a diagnostic tool for visualization of spatial autocorrelation (Anselin, 1993), Moran scatterplots were used for spatial outlier detection (Shekhar, Lu, & Zhang, 2003), to analyze categorical changes of spatial association over time (Ahn, Kim, & Lee, 2009; Rohde, Corcoran, McGee, Wickes, & Townsley, 2015), or to take into account spatial structures within choropleth map classification (Traun & Loidl, 2012).…”
Section: Autocorrelation Assessmentmentioning
confidence: 99%